2013
DOI: 10.21307/eb-2013-004
|View full text |Cite
|
Sign up to set email alerts
|

A review of restorative justice responses to offending

Abstract: The present review sought to determine on the available evidence (a) whether restorative justice (RJ) is an effective means of reducing re-offending (b) what benefits victims of crime obtain from participation in the RJ process (c) whether the public supports the principles of RJ and (d) how the cost and efficiency of RJ proceedings compare with conventional courts in cost and efficiency (i.e. time taken to finalize cases). The review finds little reliable evidence that RJ reduces re-offending. Victims who par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Hayes, 2007;Sherman and Strang, 2007;Wilson et al, 2017) contend that current evidence of RJ's crime reduction potential is promising but remains inconclusive. Still others assert that due to significant methodological limitations (Livingstone et al, 2013;McGrath, 2008;Weatherburn and Macadam, 2013), and well-known threats to validity (McCold, 2008: 9), current research lacks reliable evidence to support RJ's purported ability to reduce reoffending.…”
Section: Methodological Issues Forming An Equivalent Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayes, 2007;Sherman and Strang, 2007;Wilson et al, 2017) contend that current evidence of RJ's crime reduction potential is promising but remains inconclusive. Still others assert that due to significant methodological limitations (Livingstone et al, 2013;McGrath, 2008;Weatherburn and Macadam, 2013), and well-known threats to validity (McCold, 2008: 9), current research lacks reliable evidence to support RJ's purported ability to reduce reoffending.…”
Section: Methodological Issues Forming An Equivalent Comparisonmentioning
confidence: 99%
“…Selection bias is a widely-recognized problem within the RJ literature (Bergseth and Bouffard, 2007;Hayes, 2005Hayes, , 2007Livingstone et al, 2013;McGrath, 2008;Weatherburn and Macadam, 2013). Some comparison studies have not attempted to account or control for possible selection bias.…”
Section: The Problem Of Selection Biasmentioning
confidence: 99%
“…Alongside the flourishing of RJ programs worldwide, empirical studies have been conducted to evaluate their success. Most empirical knowledge assesses recidivism rates and the participants' level of satisfaction (Sherman et al, 2015;Weatherburn & Macadam, 2013). In general, studies have found that survivors of RJ processes benefited from and were satisfied with the process (Nascimento et al, 2022).…”
Section: The Consequences Of Youth Csvmentioning
confidence: 99%
“…Empirical studies have been conducted to evaluate the success of the growing number of RJ programs (Angel et al, 2014; Nascimento et al, 2022; Strang, 2002). Most empirical knowledge assesses recidivism rates and the participants’ degree of satisfaction (Sherman et al, 2015; Weatherburn & Macadam, 2013). In general, studies have found that survivors who took part in RJ processes were positively affected (Nascimento et al, 2022) and satisfied with the process (Latimer et al, 2005).…”
Section: Theory and Literature Reviewmentioning
confidence: 99%